The European Union's (in) Ability to Address Troubled Past (s): Voices from Eight European Countries - Zupančič, Rok; Ioannidis, Nikandros; Kocan, Faris (My University, 2021)
This paper investigates the evolution of the European Community/European Union’s (EU) ability to assist eight European countries in their attempts to address their internal historical conflicts and analyses the perceptions of people of the EU’s historical successes and eventual future role in this regard. The study applies a mixed-method approach; it employs statistical analysis of a representative survey conducted in six EU- and two non-EU member states (Germany, Ireland, Spain, Greece, Poland, Cyprus, Bosnia-Herzegovina and Kosovo; N= 6564), and combines it with the analysis of secondary and primary sources. The results indicate that several demographic characteristics of respondents (age; religion; educational level; personal experience with the events of troubled past) correlate with the assessment regarding the EU’s role in addressing troubled past in respective countries to date, as well as with the potential role the EU could have in this regard in the future.